Regulation of Ubiquitination-Mediated Protein Degradation by Survival Kinases in Cancer - Yamaguchi, Hirohito; Hsu, Jennifer; Hung, Mien-Chie (Frontiers in Oncology, 2012)
The ubiquitin-proteasome system is essential for multiple physiological processes via selective degradation of target proteins and has been shown to plays a critical role in human cancer. Activation of oncogenic factors and inhibition of tumor suppressors have been shown to be essential for cancer development, and protein ubiquitination has been linked to the regulation of oncogenic factors and tumor suppressors. Three kinases, Akt, ERK, and IKK, we refer to as oncokinases, are activated in multiple human cancers. We and others have identified several key downstream targets that are commonly regulated by these oncokinases, some of which are regulated directly or indirectly via ubiquitin-mediated proteasome degradation, including FOXO3, β-catenin, Mcl-1, and Snail. In this review, we summarize these findings from our and other groups and discuss potential future studies and applications in the clinic.